Efektifitas Penerapan Latihan Shuttle Run terhadap Kelincahan Atlet Kumite Karate SKO Provinsi Riau - Salsabilah, Salsabilah; Diyanto, Rahmad; Hilmi Wahdi, Agung; Syaputra, Aidil; Evriansyah Lubis, Ade (Jurnal Kepelatihan Olahraga, 2025)
This research aims to know the effect of shuttle run training (X) on the Agility (Y) of Kumite athletes at the Karate SKO Riau.  The method used in this research is an experimental method, with the research design used in this study is "One-Group Pretest Postest Design".  The population of this study was the Kumite Athletes Karate SKO Riau, in total 11 athletes.  The instrument that used in this study was the Dodging Run Test.  Data analysis and research hypothesis testing using independent t (t-test) with a significant level (α) of 0.05 with a confidence level of 0.95%.  Based on data analysis with the results: Pre-test average 25.9 in the Post-test 23.9 increased by 2 or 7.72% with the result (t-count 9.12 t-table 1.812), so Ho is rejected Ha accepted.  Therefore it can be concluded that shuttle run training affects the agility of Kumite Athletes Karate SKO Riau.